2019
DOI: 10.1055/a-0856-7207
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Aerobic Metabolism Responses in Endurance Athletes, Combat Athletes and Untrained Men

Abstract: This study investigated aerobic metabolism responses in trunk muscles during a prolonged trunk extension exercise in athletes and untrained young men. The aim was to analyze the adaptations induced by 2 types of sports: one involving intensive use of trunk muscles (i. e., judo), and one known to induce high aerobic capacity in the whole body (i. e., cycling). Eleven judokas, 10 cyclists and 9 healthy untrained young men performed trunk extension exercises on an isokinetic dynamometer. During the first session,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Being the components of athlete fitness general structure, parameters of physical development [1], physical [1,3,37] and functional [3,4,18,35] fitness, special work capacity [9][10][11]36] are characterized by different relationships and interactions in athletes of various skill level [2], different weight categories [3] and in the process of their sports mastery alteration [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being the components of athlete fitness general structure, parameters of physical development [1], physical [1,3,37] and functional [3,4,18,35] fitness, special work capacity [9][10][11]36] are characterized by different relationships and interactions in athletes of various skill level [2], different weight categories [3] and in the process of their sports mastery alteration [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…According to researchers reserves of anaerobic alactate, anaerobic lactacidal and aerobic energy supply systems represent the key integral indices of FF [5][6][7]. Some works show that the level of development and association of the key components of combat athlete FS tend to determine the level of their special work capacity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients then performed a five-minute isokinetic submaximal trunk extension exercise, corresponding to a constant setting torque of 80 nm, as described previously. 19 It has been established that five minutes were sufficient to permit a fully aerobic metabolic contribution, and that 80 nm corresponds to a performable and submaximal exercise level for CLBP patients (unpublished data). During this exercise, a biofeedback diagram was displayed in real time, showing the produced torque.…”
Section: Aerobic Metabolism Responses To Isokinetic Trunk Extension E...mentioning
confidence: 99%
“…In the same way, the gripping demand that occurs in the senior class shows specifics tactical arrangements with stances opposite from their opponents (kenka-yotsu) to preserve a defensive situation preceding to attack or counter-attack (Ito et al, 2019). A recent research suggested that motor action analysis in judo be conducted with consideration for sex modifications in senior combat actions with a wide range of interconnected behavior components (Sterkowicz-Przybycien et al, 2017), such as the approach action (Sterkowicz-Przybycien et al, 2017), attack with the type of technique (Anthierens et al, 2019), groundwork attempts (Brito et al, 2017) and pause phase analysis (Sterkowicz-Przybycien et al, 2017). Currently, the specific behaviors of each gender in cadet class remain unknown; this knowledge is essential to target technical-tactical training, considering each combat phase.…”
Section: Introductionmentioning
confidence: 99%